Optimal cutoff of mean corpuscular volume (MCV) for screening of alpha-thalassemia 1 trait - Chanhathai Nunchai (2020)
© 2020 Japan Society of Obstetrics and Gynecology Aim: To identify the optimal cutoff of mean corpuscular volume (MCV) for screening of alpha-thalassemia 1 trait. Methods: The database of pregnant women who attended antenatal care clinic at Department of Obstetrics and Gynecology, Chiang Mai University during January 1st, 2015 to December 31st, 2017 was accessed and reviewed. A total of 1264 cases who had MCV ≤80 fL and met the inclusion criteria were enrolled to the study. Cases with hemoglobin level ≤10.0 gm/dL, iron deficiency anemia, chronic medical diseases and other types of thalassemia trait except alpha-thalassemia 1 trait were excluded. Results: After exclusion, 438 cases were available for analysis. Of them, 139 were alpha-thalassemia 1 trait. Based on the receiver operating characteristic curves, the best cutoff value of MCV for screening of alpha-thalassemia 1 trait was ≤76.15 fL, giving 100% sensitivity, and 60.9% specificity with the area under curve of 0.925. Compared to the conventional cutoff (≤80 fL), the new cutoff gave much less false positive tests (117 vs 299 cases), whereas capability to detect alpha-thalassemia 1 trait was the same. Conclusion: With the new MCV cutoff (≤76.15 fL) as a secondary cutoff for screening alpha-thalassemia 1 carrier, a substantial number of positive cases requiring DNA analysis could be avoided without compromising the detection efficacy.